Vaccines against malaria : hope in a gathering storm - Russell, Philip K.; Howson, Christopher Paul (National Academy Press, 1996)
"Vaccines Against Malaria: Hope in a Gathering Storm" is a book that was edited by Phillip K. Russell and Christopher Paul Howson and was published in 1996 in Washington, D.C., by the National Academy Press. The book focuses on the resurgence of malaria worldwide. Malaria is a public health problem in more than 90 countries. This book includes the proceedings of a workshop that was organized by the Institute of Medicine and was held from October 19-20, 1995. The theme of the workshop was the evaluation of international efforts in malaria vaccine research and development.